A new whitish truffle, Tuber thailandicum from northern Thailand and its ectomycorrhizal association - Nakarin Suwannarach (2018)
© 2015, German Mycological Society and Springer-Verlag Berlin Heidelberg. A new species of whitish truffle, Tuber thailandicum, is described based on collections from northern Thailand. This species is characterized by whitish ascomata with dark brown gleba and subglobose spores with an alveolate reticulum. Tuber thailandicum is similar to T. castilloi, but differs in the thicker peridium and wider spores in one-spored asci. Molecular analysis of the internal transcribed spacer region and large subunit of ribosomal DNA also supports that T. thailandicum is clearly different from previously described whitish truffle species. It grows in mycorrhizal association with Betula alnoides, and the morphology and anatomy of mycorrhizae are described. Moreover, the identification of mycorrhizal status was confirmed by molecular methods.